A combination technique for edge detection (مجلة المنصور, 2022)
Interpretation of image contents is one of the objectives in computer vision specifically in image processing. In image interpretation the partition of the image into object and background is a severe step. Segmentation separates an image into its component regions or objects. Image segmentation needs to segment the object from the background to read the image properly and identify the content of the image carefully. In this context, edge detection is a fundamental tool for image segmentation. In this paper an attempt is made to study the performance of most commonly used edge detection techniques for image segmentation and also propose a mixture algorithm using edge detection for image segmentation. These methods are tested on infrared images that are an important type of images. The comparison of these techniques is carried out with an experiment.